Development of a Duplex qPCR Assay for Detecting Porcine Adulteration in Gudeg Krecek: A Complex Traditional Indonesian Food Matrix - Slamet Diah Volkandari; Siti Nurul Aisyiyah Jenie; Abdul Rohman; Yuny Erwanto (Faculty of Animal Science, Universitas Gadjah Mada, 2026)
Ensuring halal authenticity in traditional bovine hide-based products, such as Krecek (rambak cracker in Gudeg), is challenging because of the visual similarity between bovine hides and porcine skin and the severe DNA degradation caused by the intensive processing (frying and boiling in coconut milk) of these products. This study developed and validated a Duplex SYBR Green qPCR assay targeting the porcine-specific mitochondrial ND4L gene and eukaryotic 18S rRNA gene as an internal amplification control (IAC). Optimization of the primer concentrations revealed that a 2:1 ratio (ND4L:18S rRNA) provided the most balanced amplification of the target genes. The assay demonstrated high specificity, distinguishing the porcine target from the IAC by distinct melting temperatures (Tm): ND4L at 78.0°C and 18S rRNA at 85.0°C. The method was validated with a limit of detection (LOD) of 500 pg/µL, a CV of 0.60%, and specificity against 18 non-target species. An analysis of 42 commercial Krecek samples (labelled as beef) collected from traditional Gudeg vendors in Yogyakarta showed no porcine-specific melting peaks. The 100% IAC melting peak (Tm 85.0°C) was detected in all samples, confirming the successful recovery of amplifiable DNA despite the complex sample matrix. These results confirm the absence of porcine adulteration in the surveyed products and establish the proposed duplex qPCR as a robust tool for routine halal verification of highly processed, high-fat food products.